Magnetic resonance imaging studies of gastrointestinal, metabolic and appetitive responses to isoenergetic breakfasts of different plant grain origin - Alyami, Jaber (2019)
Introduction: Cereal grain based porridges are commonly consumed throughout the world. Cereal types that are popular in the Western world, such as oats and rye, have been characterised with respect to health related variables such as glycaemic response and suppression of hunger. However, other ‘ancient grains’ consumed in the Asia and in Africa, such as millets, have been studied minimally although they are believed to offer health benefits. Consuming these grains may be advantageous in the control of obesity and type 2 diabetes, the incidence of which are increasing globally. They are also a sustainable food, due to their tolerance of extreme weather and harsh growing conditions. It is thus timely to consider whether they should be exploited to a greater extent as a human food, both from a health and environmental perspective. Concurrently the development of novel magnetic resonance imaging (MRI) techniques enable a deeper understanding to be gained of the impact on health of the interaction between the GI tract and specific food. The aim of this project was thus to investigate the glycaemic, gastrointestinal, hormonal and appetitive response ratings to breakfast porridge made from different grains in healthy subjects (HVs) whilst exploiting and developing MRI.